Red-bellied black snake (Pseudechis porphyriacus) envenomation in the dog: Diagnosis and treatment of nine cases. (July 2016) - Padula, Andrew M.; Winkel, Kenneth D.
Abstract: The clinical signs, biochemical changes and serum and urine venom concentrations for a series of nine cases of Red bellied black snake [RBBS] ( Pseudechis porphyriacus ) envenomation in eight dogs seen in a regional Australian veterinary hospital are described. Although the resulting envenomation syndrome was, in most cases, relatively mild and responded rapidly to intravenous administration of a novel bivalent caprylic acid purified whole IgG equine antivenom for tiger ( Notechis scutatus ) and brown snake ( Pseudonaja textilis ), one fatality prior to antivenom treatment was recorded. The latter case occurred within 1 h of envenomation prior to receiving antivenom treatment. Intravascular haemolysis, pigmenturia, bite site swelling, lethargy, and generally mild coagulopathy were present in most cases. Detectable RBBS venom specific components were found in serum, bite site swab or urine using a standard sandwich ELISA approach. Serum levels fell within the range previously reported for human RBBS envenomation cases (6–79 ng/ml) whilst bite site and urine samples varied more markedly (8.2 to >5000 ng/ml and 2.2–1300 ng/ml respectively). No venom was detected from serum after antivenom treatment. The envenomation syndrome in dogs is similar to what is described for humans, with the exception of the presence of potentially severe venom induced consumption coagulopathy in one case (aPTT > 300 s and fibrinogen < 0.43 g/L) and potential for fatal outcomes. This series represents the largest and most detailed examination of RBBS envenomation in animals yet reported. It reinforces the emerging view that the potential severity of this envenomation has been underappreciated by veterinary practitioners and highlights the possibility of severe venom induced consumption coagulopathy in canine cases. Highlights: Case reports of dog envenomation by red bellied black snake ( Pseudechis porphyriacus ). Clinical findings, venom concentrations and laboratory changes reported. Relatively mild envenomation syndrome responding to tiger and brown snake antivenom. Death occurred in one case that did not receive antivenom treatment. Prompt recovery following antivenom administration.